SISTEM INFORMASI AUDIT MUTU INTERNAL (AMI) BERBASIS WEB DI UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI - rully pratama; Safni Marwa; Hidayati Rusnedy (Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT The quality and standards of a university play a vital role in determining graduates' success, institutional reputation, and its contribution to society. Universitas Pahlawan Tuanku Tambusai is committed to providing high-quality education through the implementation of Internal Quality Audit (AMI) conducted by the Quality Assurance Agency (LPM). However, the implementation of AMI still faces challenges such as delays in checklist submissions by study programs and manual processes in audit reporting, which affect the efficiency and accuracy of quality evaluations. To address these issues, this study proposes the development of a webbased internal quality audit information system using the prototype method. This system aims to accelerate the audit process, simplify data collection, and enhance the effectiveness and efficiency of AMI implementation at Universitas Pahlawan Tuanku Tambusai. Through the prototype approach, LPM can continuously provide feedback to ensure the developed system meets the needs and supports the enhancement of the university's quality culture. Keywords: Internal Quality Audit, Information System, Web-Based, Prototype, Quality Assurance Agency